LAW ENFORCEMENT FOR THE DESTRUCTION OF THE CULTURAL HERITAGE BUILDING EMA IDHAM’S HOUSE IN WEST SUMATRA - Nurlinda Yenti; Netra Meldi (Progressive Law Review, 2025)
The investigation into the destruction of Ema Idham's heritage building by PPNS at BPK West Sumatra is governed by Article 66 Paragraph (1) of Law No. 11 of 2010 concerning Cultural Heritage. It states that everyone is prohibited from damaging cultural heritage, whether in whole or in part, from the unit, group, or original location. The research questions are: 1) How is the investigation of the criminal act of destroying Ema Idham's cultural heritage building by PPNS at BPK West Sumatra conducted? 2) What are the obstacles faced during the investigation of this crime? 3) What efforts are being made to overcome these obstacles? This study uses a sociological-legal approach and a descriptive method. The findings are: 1) The investigation met the elements of the crime of destroying cultural heritage, but legal proceedings faced challenges because the Padang District Court canceled the suspect’s status through a pre-trial decision. 2) Obstacles include limited witnesses, investigator capabilities, and PPNS officials at BPK West Sumatra. 3) To address these issues, efforts include increasing community awareness to gather witnesses, enhancing cooperation among PPNS officials, and improving capacity through training and discussion forums.